Cooperative compliant traction mechanism for human-friendly biomechanical energy harvesting. (15th April 2022) - Zou, Hongxiang; Li, Meng; Zhao, Linchuan; Liao, Xinwen; Gao, Qiuhua; Yan, Ge; Du, Ronghua; Wei, Kexiang; Zhang, Wenming
Graphical abstract: Highlights: The concept of human-friendly biomechanical energy harvesting is proposed. A cooperative compliant traction mechanism is designed to reduce the impact on users. The mechanical modulation mechanisms are used to improve the performance. A user wearing the prototype can easily generate an average power of 0.22 W. The possibility of self-powered human-assisted system is demonstrated. Abstract: In this study, a human-friendly biomechanical energy harvester (HF-BEH) utilizing cooperative compliant traction mechanism is proposed. The knee joint is used to drive the harvester through a compliant medium without wearing any mechanical components. The driving force is large, and there is no added weight and restraint on the knee joint. The work of the harvester can naturally collaborate with the walking/running of the user due to the mechanical adaptability of the compliant medium and reasonable settings, that is, the harvester collects energy when the user does negative work. Frequency up-conversion and mechanical rectification are used to improve electromechanical conversion efficiency. A man wearing the HF-BEH prototype can generate an average power of 0.22 W while walking (4 Km/h) and 0.30 W when running (10 Km/h), with little impact on his mobility. The possibility of self-powered emergency call, positioning and tracking, health monitoring and physical therapy based on HF-BEH has been verified by powering commercial smart electronics with these functions. Human-vehicle interaction through self powered wireless sensing based on HF-BEH is demonstrated to improve the safety of people with limited responsiveness and mobility in the traffic environment. The proposed energy harvesting system can be integrated with functional modules as a self-powered human-assisted system.